Tracking the motion of charges in a terahertz light field by femtosecond X-ray diffraction. - Cavalleri, A; Wall, S; Simpson, C; Statz, E; Ward, D; Nelson, K; Rini, M; Schoenlein, R (2006)
In condensed matter, light propagation near resonances is described in terms of polaritons, electro-mechanical excitations in which the time-dependent electric field is coupled to the oscillation of charged masses. This description underpins our understanding of the macroscopic optical properties of solids, liquids and plasmas, as well as of their dispersion with frequency. In ferroelectric materials, terahertz radiation propagates by driving infrared-active lattice vibrations, resulting in phonon-polariton waves. Electro-optic sampling with femtosecond optical pulses can measure the time-dependent electrical polarization, providing a phase-sensitive analogue to optical Raman scattering. Here we use femtosecond time-resolved X-ray diffraction, a phase-sensitive analogue to inelastic X-ray scattering, to measure the corresponding displacements of ions in ferroelectric lithium tantalate, LiTaO(3). Amplitude and phase of all degrees of freedom in a light field are thus directly measured in the time domain. Notably, extension of other X-ray techniques to the femtosecond timescale (for example, magnetic or anomalous scattering) would allow for studies in complex systems, where electric fields couple to multiple degrees of freedom.